Pengaruh Pemahaman Peraturan Perpajakan, Sosialisasi Perpajakan, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak (Studi Pada Pelaku Ekonomi Kreatif Sub Sektor Blended Kuliner dan Fashion di Kabupaten Malang) - Anil Hidayati Rohmah; Jeni Susyanti; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to determine the effect of understanding tax regulations, tax socialization, and tax sanctions on individual taxpayer compliance with creative economy actors in the blended culinary and fashion sub-sector in Malang Regency. Determination of the sample in this study using purposive sampling technique, so that the number of samples can be determined as many as 40 respondents who meet the criteria. The analytical tool used in this research is multiple linear regression analysis. The results showed that the understanding of tax regulations, tax socialization, and tax sanctions simultaneously had a significant effect on taxpayer compliance with the mixed creative economy actors of the fashion and culinary sub-sectors in Malang district. The variable of understanding tax regulations has a significant and positive effect on individual taxpayer compliance of creative economy actors in the blended culinary and fashion sub-sector in Malang Regency. The tax socialization variable has a significant and positive effect on individual taxpayer compliance of creative economy actors in the blended culinary and fashion sub-sector in Malang Regency. The variable of tax sanctions has no effect on taxpayer compliance on the creative economy actors in the blended culinary and fashion sub-sector in Malang Regency.Keywords: Creative Economy in Blended Culinary and Fashion Sub-Sector in Malang Regency, Understanding of Tax Regulations, Tax Socialization, Tax Sanctions, Taxpayer Compliance.